The Urgency Of Blockchain In Developing The Tourism Industry In Indonesia - Didik Supriyanto; Eva Desembrianita; Donny Juliandri Prihadi; Dyah Ayu Suryaningrum; Bambang Amir Alhakim (Jurnal Teknologi dan Manajemen Industri Terapan, 2025)
This study is a qualitative study with a descriptive approach. It relies on descriptive text to express this article's primary intent and purpose by first describing the main topics, including Blockchain, the Tourism Industry, and its development through Blockchain. The data used in this study are primary data that researchers obtain from various credible sources such as books, scientific magazines, scientific articles, and other sources, which are usually used in each study. The data obtained are analyzed using the stages of data collection, reduction, selection, and conclusion. The result in this article shows that Blockchain can develop the tourism industry in Indonesia through the ease of booking tickets and finding tourist locations, security of tourist data, both foreign and local, tourism marketing, ease of tourism payments, and so on, which aim to develop the tourism industry in Indonesia.